Methicillin-Resistant Subspecies Infection in a Patient With Hepatocellular Carcinoma - Thein Swe MD; Akari Thein Naing MD; AAMA Baqui MD PhD; Ratesh Khillan MD (SAGE Publishing, 2016)
To our knowledge and literature search, Staphylococcus schleiferi subspecies coagulans infection in human beings has rarely been described in the medical literature. Furthermore, we believe that this is a first detailed case report of methicillin-resistant Staphylococcus schleiferi subspecies coagulans infection in a patient with hepatocellular carcinoma. Because of the possible association of Staphylococcus schleiferi infection and immunosuppression, any isolates of this bacterium in human beings should be presumed to be pathogenic, unless proven otherwise.